The Construction of Female Anti-Hero Identities Analyzing the Gender Roles of Eve and Villanelle in Killing Eve - H. L. Eklund (Studies in Social Science & Humanities, 2024)
This paper explores the groundbreaking portrayal of female anti-heroes in Killing Eve through an analysis of the gender roles and moral complexities of its central characters, Eve Polastri and Villanelle. The series dismantles traditional archetypes of femininity, replacing them with dynamic, morally ambiguous identities that challenge societal norms and narrative conventions. Eve’s transformation from an unassuming intelligence officer to an ethically flexible anti-heroine parallels Villanelle’s unapologetic embrace of power and chaos, creating a multifaceted narrative that redefines the anti-hero archetype. Their relationship, marked by obsession, attraction, and mutual recognition, transcends conventional tropes, offering a nuanced exploration of identity, power, and agency. By refusing to impose judgment on its characters, Killing Eve elevates female representation, allowing its protagonists to inhabit spaces of complexity and contradiction. This paper argues that the series not only expands the possibilities for female narratives but also disrupts traditional gendered associations with morality, power, and storytelling.